Synthesis of Tolmetin Hydrazide-Hydrazones and Discovery of a Potent Apoptosis Inducer in Colon Cancer Cells - ÖZSAVCI, DERYA; ORUN, OYA; BİNGÖL ÖZAKPINAR, ÖZLEM; SÜZGÜN, PELİN; MEGA TİBER, PINAR; ERDEM, SAFİYE; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (WILEY-V C H VERLAG GMBH, 2015)
Tolmetin hydrazide and a novel series of tolmetin hydrazide-hydrazones 4a-l were synthesized in this study. The structures of the new compounds were determined by spectral (FT-IR, H-1 NMR) methods. N-[(2,6-Dichlorophenyl)methylidene]-2-[1-methyl-5-(4-methylbenzoyl)-1H-pyrrol-2-yl]acetohydrazide (4g) was evaluated in vitro using the MTT colorimetric method against the colon cancer cell lines HCT-116 (ATCC, CCL-247) and HT-29 (ATCC, HTB-38) to determine growth inhibition and cell viability at different doses. Compound 4g exhibited anti-cancer activity with an IC50 value of 76M against colon cancer line HT-29 (ATCC, HTB-38) and did not display cytotoxicity toward control NIH3T3 mouse embryonic fibroblast cells compared to tolmetin. In addition, this compound was evaluated for caspase-3, caspase-8, caspase-9, and annexin-V activation in the apoptotic pathway, which plays a key role in the treatment of cancer. We demonstrated that the anti-cancer activity of this compound was due to the activation of caspase-8 and caspase-9 involved in the apoptotic pathway. In addition, in this study, we investigated the catalytical effect of COX on the HT-29 cancer line, the apoptotic mechanism, and the moleculer binding of tolmetin and compound 4g on the COX enzyme active site.
Keywords: Apoptosis; Caspase-3; Colon cancer; Hydrazide-hydrazone; Tolmetin; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; COLORECTAL-CANCER; ANTI-HCV; BIOLOGICAL-ACTIVITIES; PRO-APOPTOSIS; ASPIRIN USE; IN-VITRO; COX-2; DERIVATIVES; ANTICANCER